2023
DOI: 10.3390/antiox12061311
|View full text |Cite
|
Sign up to set email alerts
|

Whey Improves In Vitro Endothelial Mitochondrial Function and Metabolic Redox Status in Diabetic State

Abstract: Endothelial dysfunction plays a critical role in the progression of type 2 diabetes mellitus (T2DM), leading to cardiovascular complications. Current preventive antioxidant strategies to reduce oxidative stress and improve mitochondrial function in T2DM highlight dietary interventions as a promising approach, stimulating the deepening of knowledge of food sources rich in bioactive components. Whey (WH), a dairy by-product with a considerable content of bioactive compounds (betaines and acylcarnitines), modulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…We found that iSGLT2 promoted lysosome accumulation and autophagy cell death via LC3B activation in CRC cells and along with ER stress induction and upregulation of the molecular players related to autophagy triggered by ER stress, namely ER-phagy, i.e., PERK, CHOP and ATF6 [ 45 , 67 , 68 ]. Several reports described the ER stress-mediated autophagy-associated cell death as antitumor strategies in CRC [ 39 , 69 71 ]. However, to date no studies explored the association between SGLT2 and ER stress/autophagy as antineoplastic tool in CRC.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We found that iSGLT2 promoted lysosome accumulation and autophagy cell death via LC3B activation in CRC cells and along with ER stress induction and upregulation of the molecular players related to autophagy triggered by ER stress, namely ER-phagy, i.e., PERK, CHOP and ATF6 [ 45 , 67 , 68 ]. Several reports described the ER stress-mediated autophagy-associated cell death as antitumor strategies in CRC [ 39 , 69 71 ]. However, to date no studies explored the association between SGLT2 and ER stress/autophagy as antineoplastic tool in CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic state was investigated by using Glucose Assay Kit-WST (Dojindo Molecular Technologies, Tokyo, Japan), Lactate Assay Kit-WST (Dojindo, Molecular Technologies, Tokyo, Japan), NAD/NADH Assay Kit-WST (Dojindo Molecular Technologies, Tokyo, Japan), GSSG/GSH quantification kit (Dojindo Molecular Technologies, Tokyo, Japan), and ATP kit (Abcam, Cambridge, UK), according to the supplier’s instructions and as already described [ 38 , 39 ]. Specific absorbances were measured with a microplate reader model 680 (Bio-Rad, Hercules, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations